Guidelines for Transparency on Gut Microbiome Studies in Essential and Experimental Hypertension. Issue 6 (December 2019) - Marques, Francine Z.; Jama, Hamdi A.; Tsyganov, Kirill; Gill, Paul A.; Rhys-Jones, Dakota; Muralitharan, Rikeish R.; Muir, Jane; Holmes, Andrew; Mackay, Charles R.
Abstract : Hypertension is a complex and modifiable condition in which environmental factors contribute to both onset and progression. Recent evidence has accumulated for roles of diet and the gut microbiome as environmental factors in blood pressure regulation. However, this is complex because gut microbiomes are a unique feature of each individual reflecting that individual's developmental and environmental history creating caveats for both experimental models and human studies. Here, we describe guidelines for conducting gut microbiome studies in experimental and clinical hypertension. We provide a complete guide for authors on proper design, analyses, and reporting of gut microbiota/microbiome and metabolite studies and checklists that can be used by reviewers and editors to support robust reporting and interpretation. We discuss factors that modulate the gut microbiota in animal (eg, cohort, controls, diet, developmental age, housing, sex, and models used) and human studies (eg, blood pressure measurement and medication, body mass index, demographic characteristics including age, cultural identification, living structure, sex and socioeconomic environment, and exclusion criteria). We also provide best practice advice on sampling, storage of fecal/cecal samples, DNA extraction, sequencing methods (including metagenomics and 16S rRNA), and computational analyses. Finally, we discuss the measurement of short-chain fatty acids, metabolites produced by the gut microbiota, and interpretation of data. These guidelines should support better transparency, reproducibility, and translation of findings in the field of gut microbiota/microbiome in hypertension and cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.